English Verb Errors in Students’ Proposal Drafts by English Department Students of Universitas Balikpapan - Arrum Wirawati (Pendidikan Bahasa Inggris (Universitas Internasional Batam), 2017)
The purpose of this study is to investigate and classify English verb errors which made on students’ proposal drafts by sixth semester at the English department students. Besides, this study aims to find out their frequency in writing. The method used in this study is quantitative. The result of the error analysis process shows that students committed errors into 6 types of verb errors and 4 types of errors which are omission, misordering, misinformation, and addition. The most often committed verb error made by student is auxiliary with 30.30%, followed by transitive error with 24.24%, 21.21% for verb tense error, 15.15% for intransitive error, 6.07% for to infinitive error, and the lowest percentage fall into passive voice error with 3.03%. It proves that students still have difficulty in writing using grammatical correctly.